Factors Affecting Consumers’ Purchase Intentions Towards Recycled Products - Esmat, Sherine (AUC Knowledge Fountain, 2023)
The work executed addresses the status of recycling industry in Egypt and its relation to the current sustainability trends as well as climate change issues. It also identifies the main concerns of consumers when purchasing recycled products. Consequently, identifies the key pillars that need to be applied or communicated with the target consumers to enhance the concept of selling recycled products and increase its market share. Since this industry is significantly broad, the focus of the study was only on recycled PET plastic bottles (rPET), this is to ensure attaining accurate and reliable results. An interview and a site visit were conducted with the main and only producer of rPET in Egypt and MENA region, BariQ. Unveiling the recycling industry’s details starting from the primary source, revealing its struggles and benefits. Another two interviews were conducted with two selected secondary producers, the first is L’Oreal, focusing on their recycled shampoo bottles. The second is Nestle, focusing on their recycled water bottles. This is to get an overview on their market performance besides spotting their challenges and needs. After that, an online survey was constructed, targeting potential consumers of the mentioned brands to pinpoint the main factors affecting their purchase actions towards recycled products. Mainly questioning if the main factors were the brand, price, quality, an unknown feeling or other factors. The results showed that the producers are exerting huge efforts to improve the market of recycling, but are not receiving enough support from their consumers. They seek to have an identified system and clear frameworks to work with, in order to gain control on the whole process. Regarding the consumers insights, the survey results showed significant low awareness on Nestle’s water bottle to be only 24%, even though they created an online campaign. While L’Oreal got a mere 8.5% for awareness, which was due to not advertising for it, it was only claimed on the bottle. Even though the awareness is low, but supporting the idea of having recycled products in the market reached 75%, which is significantly high, specifically with a greater support for the recycled shampoo bottles. Consumers’ main concerns when purchasing Nestle’s recycled bottles were: 1. Quality, 2 & 3 Price and Brand. While the main concerns for L’Oreal’s recycled bottles were: 1. Effectiveness of shampoo, 2. Brand and 3. Price. Noting that the “Brand” of the product is in the top three requirements needed for making a purchase decision. This supports the stated hypothesis. Innovative marketing methods are recommended to ensure eliminating all the negative perceptions of consumers. Mainly by raising awareness on the recycled products, through discussing the key messages generated from the survey reflecting the consumer’s priorities, expectations and main concerns towards each specific recycled product. Execution can be through a mix of offline and online marketing channels. Eventually, the consumer should feel that purchasing recycled products is an action that creates a shared value and positively contributes to the development of the economy, environment and society.